Synchronicity of global construction cost indexes. Issue 3 (28th February 2019) - Zhang, Ruixi; Xing, Jinding; Ye, Kunhui; Lu, Weisheng; Shan, Yongwei
Abstract : Purpose: The purpose of this paper is to examine the features and tendency of cost indices in the global construction setting. Design/methodology/approach: Data from 22 countries/regions are collected and analyzed using maximum variance formulation and Kendall rank correlation coefficient. Findings: It is found that global construction cost indexes (CCIs) have commonly maintained a steady increase for decades, and the CCIs synchronize with each other. Overall synchronicity and synchronicity of different countries pairs have increased with time significantly. Research limitations/implications: The major limitation, however, is the availability of data: only 22 regions/countries are examined, the distribution of these regions/countries is imbalanced between different continents and various indices are adopted around the world, of which statistical methods are not same. Practical implications: The implication is that a better perception of CCIs enables contractors to have a robust estimation for bidding prices and to improve the efficiency of construction projects management. The research findings also provide a useful reference for those countries that have not established construction cost indices databases to forecast the tendency of domestic construction industries. Originality/value: This paper contributes to the overall body of knowledge by presenting the co-movement of global CCIs and measuring the changes of CCI synchronicity with time and in different countries pairs.